Metabolic and stress responses in dairy cows fed a concentrate-rich diet and submitted to intramammary lipopolysaccharide challenge. (12th September 2017) - Aditya, S.; Humer, E.; Pourazad, P.; Khiaosa-ard, R.; Zebeli, Q.
Abstract : Feeding dairy cows diets rich in grain often leads to subacute rumen acidosis (SARA), which might affect their responsiveness to immunogenic stimuli such as exogenous lipopolysaccharide (LPS), and can lead to metabolic alterations. The main objective of this study was to investigate if SARA affects the stress and metabolic health responses resulting from an intramammary LPS challenge. Before the intramammary LPS challenge, the SARA cows showed higher blood glucose and a tendency for higher lactate and aspartate aminotransferase as well as a trend toward lower β -hydroxybutyrate (BHBA) and γ -glutamyltransferase compared with control cows. After the LPS challenge, the serum cortisol concentration markedly increased and the calcium concentration decreased both in SARA and control cows. In SARA-LPS cows, however, the lactate concentration increased due to the LPS infusion, whereas it remained unchanged in the control cows. A lower serum BHBA concentration was found in SARA-LPS compared with control-LPS cows. Higher non-esterified fatty acid concentrations were found in control-LPS cows shortly before the LPS challenge compared with SARA cows, challenged or not with LPS, whereas it did not differ from SARA-LPS cows thereafter. In conclusion, the results suggest that intramammary LPS challenge induced stress and lowered calcium concentration in all dairy cows, whereby this challenge showed lower BHBA and higher lactate levels in cows with SARA conditions.